INFLUENCE OF INTEGRITY, TEAMWORK, COMPETENCE, AND MANAGERIAL ABILITY ON EMPLOYEE WORK PRODUCTIVITY AT THE OFFICE OF SINGKEP SELATAN DISTRICT, LINGGA REGENCY - Kurniawan, E. Dody; Hariono, Desrian; Purwadi, Purwadi; Suyono, Suyono; Sumardin, Sumardin (International Journal of Multidisciplinary Research and Literature, 2024)
This study analyzes the influence of integrity, teamwork, and competence on employee work productivity. The study population consisted of 37 employees, and the data were analyzed using the regression method. The results show that the integrity variable (X1) significantly influences work productivity with a determination coefficient of 66.1%, meaning that 66.1% of the variation in work productivity can be explained by integrity. The teamwork variable (X2) also has a significant influence with a determination coefficient of 53.7%, indicating that teamwork explains 53.7% of the variation in work productivity. Meanwhile, competence (X3) has a lower influence on work productivity, with a determination coefficient of 27.0%. The t-test shows that the integrity and teamwork variables significantly influence productivity, while competence shows a more limited influence. As a result, this study emphasizes the significance of integrity and teamwork in enhancing employee productivity, even though competence also plays a more limited role in this context